2010
DOI: 10.1111/j.1365-313x.2009.04026.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the catalytic subunit of DNA polymerase α influences transcriptional gene silencing and homologous recombination in Arabidopsis

Abstract: SUMMARYREPRESSOR OF SILENCING 1 (ROS1) encodes a DNA demethylase that actively removes DNA methylation. Mutation in ROS1 leads to transcriptional gene silencing of a T-DNA locus that contains two genes, RD29A-LUC and 35S-NPTII, originally expressed in the C24 wild type. These units have different silencing regulation mechanisms: the former mechanism is dependent on small interfering RNA (siRNA)-directed DNA methylation, but the latter is not. We studied the latter gene silencing mechanism by screening the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 32 publications
7
81
0
Order By: Relevance
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, pold2-1 had little effect on the ProRD29A:LUC locus in dms3-4. Like mutants of DNA replication-related proteins (Elmayan et al, 2005;Xia et al, 2006;Yin et al, 2009;Liu et al, 2010aLiu et al, , 2010b, pold2-1 failed to suppress the silenced ProRD29A:LUC in the ros1-1 mutant (Fig. 1F).…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the POLA1 gene, also known as INCURVATA2 (ICU2), was originally identified in a genetic screen for abnormal leaf morphology and has a role in transcriptional silencing (Barrero et al 2007;Liu et al 2010a). The sequence features of POLA1 are conserved with the exception of a YYRRLFP motif of unknown function present in yeast and animal POLA4 subunit but not in plants (Shultz et al 2007).…”
Section: Polamentioning
confidence: 99%